EFFECT OF DIETARY IRON IN PRESENCE OF SULPHUR ON SOME LIVER MINERAL CONCENTRATIONS AND PERFORMANCE OF GROWING LAMBS - Sefdeen, S. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The effect of two levels of dietary iron (Fe) in presence of three levels of sulphur (S) on Cu status and performance of growing lambs was examined using 37 weaned Texel-cross over the period of 12 weeks. The basal diet (L:L) contained no Fe or S supplement; H:M diet supplemented with 800 mg Fe/kg DM and 1.5 g S/kg DM, and H:H diet was supplemented with 800 mg Fe/kg DM and 3.5 g S/kg DM. The concentrate diet was based on dried grass nuts and barely designed for lambs to grow at the rate of 200 g d-1. The results revealed that dietary treatments had no effects on DMI, DWG, final weight, total weight gain, and FCE of lambs. The lambs fed L:L diet trended (P=0.057) to have a higher plasma Cu concentrations (12.11 µmol l-1) than those fed H:M (10.78 µmol l-1) or H:H (10.38 µmol/l) diets at week 12. Dietary treatments had no effect on hepatic Cu, Mn, Mo, and Zn concentration at week 12. However, the lambs fed H:M or H:H had higher hepatic Fe (P=0.05) concentrations than those fed L:L diet. In conclusion, supplemental Fe and S had no effects on lamb performance, but decreased plasma Cu concentrations and increased plasma Mo concentrations of growing lambs. Supplemental Fe and S reduced hepatic Cu concentration of lambs compared with those fed no Fe and S supplements but the difference lacked significance.